EXPLORING THE IMPACT OF DIGITAL STORYTELLING ON READING AND CRITICAL THINKING: A PRELIMINARY STUDY - Nur Shafiekah Sapan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The Reading and Writing classroom introduces a digital storytelling project to engage students in meaningful learning experiences. Digital storytelling integrates multimedia elements such as images, audio, and video with narrative structures, offering an engaging and interactive approach to language learning. By immersing English as a Second Language (ESL) learners in rich, contextually relevant stories, digital storytelling can cater to diverse learning styles and promote a deeper understanding of textual content. This study investigated students’ perceptions of digital storytelling projects and their potential impact on reading and critical thinking skills in Reading and Writing classrooms. This preliminary study involved 64 first-year ESL students from Universiti Malaysia Sabah Labuan International Campus. The data gathered from the study were taken through a mixed-method approach, combining questionnaires and qualitative feedback from the participants. The data analysis revealed that students generally had positive perceptions of the project, with most participants agreeing that the digital storytelling project enhanced their reading comprehension, critical thinking, and creativity. The study suggests that digital storytelling can be a valuable tool for developing reading skills and higher-order thinking in ESL learners. Future research is needed to explore digital storytelling projects’ long-term effects on reading and critical skills.